Anticipation of the entry and spread of Equine Infectious Anemia in Horses in Indonesia - Muharam Saepullah; Indrawati Sendow; Atik Ratnawati; NLP Indi Dharmayanti (Indonesian Center for Animal Research and Development, 2019)
Horse is an attractive commodity in the world of horse matches, both for horse racing and equistrian. Recently, Asian countries including Indonesia have conducted international horse races. Horse traffic from several countries is unavoidable. This movement can lead to the entry of new diseases or the transmission of imported horses from local horses. At present, data on horse disease in Indonesia has not been widely reported, including Equine Infectious Anemia (EIA). This paper discusses EIA disease in horses about the etiology, characterization, spread of disease, its status in Indonesia and its treatment. EIA is a chronic disease characterized by high fever and thrombocytopenia. One of the factors that spread EIA infection, namely through traffic or horse movements. The highest risk factors for the spread of EIA disease are in the equestrian sector, followed by horse as a hobby, horse show or fattening horses for consumption. Wet environmental factors have higher risk to infection than dry areas. Applying the proper quarantine system, monitoring horse disease through surveillance, and implementing biosecurity at farms, location of events and at veterinary clinics, need to be done so that the entry of EIA disease can be anticipated as early as possible. This paper is expected to be useful and can be used as input for policy makers in the horse imports and movement.